2021
DOI: 10.1177/0194599821990682
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Reconstruction of Osteonecrosis: Assessment of Long‐term Quality of Life

Abstract: Objective Review long-term clinical and quality-of-life outcomes following free flap reconstruction for osteonecrosis. Study Design Retrospective multi-institutional review. Setting Tertiary care centers. Methods Patients included those undergoing free flap reconstructions for osteonecrosis of the head and neck (N = 232). Data included demographics, defect, donor site, radiation history, perioperative management, diet status, recurrence rates, and long-term quality-of-life outcomes. Quality-of-life outcomes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…There was a significant difference in preoperative versus postoperative swallowing function, with an absolute improvement of 11% in patients eating a regular diet, but no difference in gastrostomy tube dependency. This is consistent with Sweeny et al, who reported 15% and 26% of patients reported improved diet function at 3 months and 5 years, respectively 33 . Despite no significant improvement in gastrostomy tube dependency, the postoperative gastrostomy tube dependency rate was 23%, which compares favorably to the reported 34% gastrostomy tube dependency rate for major oral cavity cancer ablative and reconstructive surgery 34 …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…There was a significant difference in preoperative versus postoperative swallowing function, with an absolute improvement of 11% in patients eating a regular diet, but no difference in gastrostomy tube dependency. This is consistent with Sweeny et al, who reported 15% and 26% of patients reported improved diet function at 3 months and 5 years, respectively 33 . Despite no significant improvement in gastrostomy tube dependency, the postoperative gastrostomy tube dependency rate was 23%, which compares favorably to the reported 34% gastrostomy tube dependency rate for major oral cavity cancer ablative and reconstructive surgery 34 …”
Section: Discussionsupporting
confidence: 88%
“…While IMRT may reduce the risk of ORN, once ORN develops, it is unclear if patients who had been treated with IMRT have differing outcomes 3,9 . This study does not assess biochemical measures of morbidity, such as malnutrition or hypothyroidism, which would aid in the quantification patients' underling poor health 33 . Postoperative functional measures were the final assessment performed for each patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, patients with advanced osteoradionecrosis often present with severe pain, draining fistulas, or pathologic fractures. These sequelae reduce the patient's quality of life secondary to chronic pain, inability to tolerate oral intake, and social anxiety 1,2 …”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study found that patients who received pentoxifylline and tocopherol after radiation had a lower incidence of ORN [20] . Dissard et al [21] also found that administration of the PENTOCLO regimen daily had a low side effect profile with high rates of symptom improvement when given antibiotics and steroids.…”
Section: Non-surgical Managementmentioning
confidence: 98%